Entrepreneurial Competence in Vocational Fashion Education: A Comparative Study of Alumni Across Educational Levels in West Sumatra from A Values Based Islamic Perspective - Hadiastuti Hadiastuti; Ganefri Ganefri; Asmar Yulastri; Yuliana Yuliana; Ambiyar Ambiyar; Fadhilah Fadhilah (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study investigates entrepreneurial competence among vocational fashion education alumni and examines the role of Islamic values in strengthening such competence across educational levels. Using a convergent mixed-methods design, data were collected from 90 alumni entrepreneurs in West Sumatra (30 from vocational secondary schools, 30 diploma, and 30 bachelor graduates) through questionnaires and semi-structured interviews. Quantitative data were analyzed using descriptive statistics and one-way ANOVA, while qualitative data were examined through thematic analysis. The findings reveal that overall entrepreneurial competence is high across groups, with significant differences based on educational level (F(2,87) = 9.53, p .001). Bachelor’s degree graduates demonstrate stronger strategic competencies, particularly in networking, management, and opportunity recognition, whereas vocational secondary graduates show comparable strengths in persistence and production skills. Qualitative results indicate that Islamic values—such as honesty (ṣidq), trustworthiness (amānah), perseverance (istiqāmah), and sincerity (ikhlāṣ)—serve as internal mechanisms that reinforce ethical behavior, motivation, and business sustainability. The study concludes that entrepreneurial competence is both developmentally structured and value-reinforced, highlighting the importance of vertically aligned, experience-based, and values-integrated curricula. However, the study is limited by its regional scope and cross-sectional design. Future research should expand to broader contexts and explore longitudinal and sector-specific applications of values-based entrepreneurship education.